Ações dúplices - Pezzotti, Olavo José Justo (2007)
The theme related with the attitudes or positionings that the defendant can adopt in the civil process, especially in the ordinary procedure, is quite vast and complex. Multiples are the possibilities introduced to the defendant, both to attack the procedural relationship or to refute the merit, direct or indirectly. The hypotheses that allow to the defendant exceptionally to present counterattack to the author s pretension, or to obtain for himself court protection of merit, demand requirements and present convergent characteristics and others that differentiate them. Among the cases before referred, this work approaches the denominated action duplex and counterclaim. In an perfunctory exam of these afirmations, it could be considered redundant to treat the action duplex and the counterclaim, since they would be synonymous or related institutes. In order to reach the desideratum of distinguishing the several species of defendant s counterattack and their implications related to the litigious object of the process, the dissertation was divided in four chapters. In the first chapter, it approaches the contradictory and the wide defense, the defendant s legitimacy and the eventual interference of the positionings by him adopted on the litigious object. In the second, it discourses on the several attitudes that the defendant can adopt in the civil process. In the third chapter, it examines the action duplex, both in the Civil Process Code and in the extravagant procedural legislation. In the fourth chapter, it approaches the counterclaim, comparing the convergence points and divergencies among the counterclaim species foreseen for using by the defendant. In the conclusions, it detaches the common points and divergencies between the action duplex and the other hypotheses that permit the defendant to formulate a request to obtain for him a life good, confronting them with the counterclaim, as well as the implication, application and its relationship with institutes like provisional remedy, default, reconvention and others